Improving SME Performance Through the Utilization of Usable Digital Technology in the Gunung Kawi Area, Wonosari, Malang - Winarno, agung; Aini, Desti Nur (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2024)
The development of digital technology has changed the way society consumes information and makes decisions, including in the tourism sector and other related fields, including small and medium enterprises (SMEs) around the tourist areas. The Mount Kawi area, known for its religious tourism, natural beauty, and cultural heritage, seems to continue to attract visitors even though it has not fully recovered as it was before the Covid-19 pandemic. This also impacts the development of the performance of existing SMEs. This community service aims to introduce user-friendly digital marketing technology to small and medium enterprises (SMEs), so they do not have to rely solely on the local market. The approach used is the initiation model, which involves stages of introduction, demonstration, evaluation, improvement, and reinforcement. The participants of the event consisted of 20 SMEs, ranging from batik to various types of food. The instruments for success used are observation sheets and portfolios. The results of the activities show an increase in digital knowledge among SMEs, particularly in utilizing social media for product content that supports online marketing strategies, as well as the ability to create content and operate digital technology based on market feasibility. The recommendation from this community service activity is the need for assistance in certifying their products to enhance consumer trust.